2017
DOI: 10.3389/fpsyg.2017.00753
|View full text |Cite
|
Sign up to set email alerts
|

Yes: The Symptoms of OCD and Depression Are Discrete and Not Exclusively Negative Affectivity

Abstract: Although Obsessive-Compulsive Disorder (OCD) and Depression are classified as separate disorders, the high incidence of co-morbidity and the strong correlations between measures of each has led to debate about the nature of their relationship. Some authors have proposed that OCD is in fact a mood disorder while others have suggested that the two disorders are grounded in negative affectivity. A third proposition is that depression is an essential part of OCD but that OCD is a separate disorder from depression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 91 publications
0
8
0
1
Order By: Relevance
“…Some studies indicated that anger and anger suppression could be moderated by depressive symptoms, as relationships between OCD and anger were no longer significant after controlling for depression [11,13]. However, by controlling for depressive symptoms it is likely that relevant variance in the relationship between OCD and anger is removed (see [49]). Also, many patients were medicated, mostly with antidepressants (SSRIs).…”
Section: Limitationsmentioning
confidence: 99%
“…Some studies indicated that anger and anger suppression could be moderated by depressive symptoms, as relationships between OCD and anger were no longer significant after controlling for depression [11,13]. However, by controlling for depressive symptoms it is likely that relevant variance in the relationship between OCD and anger is removed (see [49]). Also, many patients were medicated, mostly with antidepressants (SSRIs).…”
Section: Limitationsmentioning
confidence: 99%
“…For example, people with obsessive-compulsive disorder and major depressive disorder have lower levels of competence in dealing with people, social interactions, and work ( Moritz et al, 2018 ; El-slamon et al, 2022 ). People with depression also experience high anxiety levels, such as agitation, apprehension, and worry ( Moore and Howell, 2017 ). Depression is related to strong negative emotions, including panic, anger, sadness, loneliness, self-blame, and resentment.…”
Section: Review Of Literaturementioning
confidence: 99%
“…At the same time, weak negative emotions include calmness and relaxation. These negative emotions elaborate on the different emotional manifestations of obsessive-compulsive disorder (OCD) and depression ( Moore and Howell, 2017 ). and it is evident from many survey data that depression is diagnosed simultaneously as at least one-third of OCD patients are diagnosed ( Nestadt et al, 2001 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Gejala lain bisa berupa rasa lelah yang ditandai dengan gejala somatik (misalnya: sakit kepala) yang muncul dapat berupa kelelahan dengan gejala somatik. Wheaton (2007) (Koran dkk, 2007;Moore & Howell, 2017;Moroney, 2017;Pigot dkk, 1994). Kondisi ini serupa dimana kecemasan dan depresi merupakan aspek distress yang diukur dengan menggunakan HSCL-25 dan terbukti keduanya memiliki skor yang tinggi.…”
unclassified